REFORMASI SISTEM PERIZINAN BERBASIS RISIKO DAN IMPLIKASINYA TERHADAP KEPASTIAN HUKUM DI INDONESIA - I Wayan Kartimin; IM. ArjayaIM. Arjaya; I Wayan Terimajaya (Universitas Mahendradatta, 2026)
The licensing system in Indonesia has undergone a fundamental transformation through Law Number 6 of 2023 concerning Job Creation, which introduced a risk-based licensing approach. This study analyzes the concept, implementation mechanisms, and implications of the risk-based licensing system for legal certainty in Indonesia. A normative legal research method was used, with both statutory and conceptual approaches. The results show that the risk-based licensing system classifies business activities into four risk levels with varying requirements, integrated within the OSS system to improve the ease of doing business. The implications for legal certainty are ambivalent: positive in the form of simplified procedures, standardized requirements, and increased predictability; but also creating uncertainty in risk assessment criteria, regulatory inconsistencies, a shift from preventive to repressive approaches, and weak oversight. Key challenges include regulatory harmonization, institutional capacity, compliance culture, and the balance between ease of doing business and protecting the public interest. The study recommends regulatory refinement, institutional strengthening, increased oversight, transparency, public participation, continuous evaluation, and a strengthened compliance culture to ensure legal certainty in the risk-based licensing system.